Think facility, act on integrity. Issue 3 (26th December 2016) - Wasileski, Robert F.
Abstract : The Chemical Processing Industry (CPI) has witnessed growth in Mechanical Integrity (MI) programs, which have evolved from standards‐based compliance, to continuous improvement programs, and on to risk‐based programs. For instance, operators (i.e., manufacturers) have redesigned corporate standards, plant‐level procedures and field practices to keep pace with incident learnings and recommended practices, such as those espoused by the American Institute of Chemical Engineers' (AIChE) Center for Chemical Process Safety (CCPS). Furthermore, the property insurance industry has duly taken note of this MI evolution, giving rise to a significantly greater focus on MI programs during insurance surveys and inspections. Meanwhile, incident investigators remain in demand as incidents with MI‐related causes continue to occur in the CPI. This apparent disconnect naturally raises questions in regards to subjects such as "risk based inspection (RBI), " "reliability centered maintenance (RCM), " "industry best practice, " and "inspection, testing and preventive maintenance (ITPM)." MI programs play a considerably important role in the process safety lifecycle of equipment. The engineering design phase of a project may be on the order of just days, up to several years for a complete plant. Procurement and construction typically follow a similar timeline proportionate with the engineering design phase. However, once a facility becomes fully operational, the time devoted toward operation and maintenance will normally far out‐weigh the engineering, procurement and construction (EPC) period, and may last for many decades. As such, the process safety equipment lifecycle (PSEL) may be largely governed by the MI program. The PSEL is explained in this article, with an examination of the central elements which should be embraced by a comprehensive MI program. While the article demonstrates the breadth and depth of MI, it aptly proposes a practical approach toward the management system that forms the foundation of a robust MI program. The proposed framework leverages the Onion Skin diagram in the context of the equipment lifecycle to create an intuitive approach to MI management. This management system framework is comprehensive, sound, and practical for implementation at facilities of most any size. © 2016 American Institute of Chemical Engineers Process Saf Prog 36: 264–272, 2017